Higher risk of incident hepatitis C virus among young women who inject drugs compared with young men in association with sexual relationships: a prospective analysis from the UFO Study cohort - Tracy, Daniel (BMJ Publishing Group, 2014)
BACKGROUND: Female injection drug users (IDUs) may report differences in injection behaviours that put them at greater risk for hepatitis C virus (HCV). Few studies have examined these in association with HCV incidence. METHODS: Longitudinal data from a cohort of 417 HCV-uninfected IDU aged 30 or younger were analysed. Cox proportional hazards was used to model female sex as a predictor of new HCV infection. General estimating equation (GEE) analysis was used to model female sex as a predictor of HCV-associated risk behaviour prospectively. RESULTS: Women were significantly more likely than men to become infected with HCV during study follow-up (HR 1.4, p<0.05), and were also more likely than men to report high-risk injecting behaviours, especially in the context of sexual and injecting relationships. Sex differences in injecting behaviours appeared to explain the relationship between sex and HCV infection. CONCLUSIONS: Young women’s riskier injection practices lead to their higher rates of HCV infection. Further study on the impact of intimate partnership on women’s risk behaviour is warranted.